Health behaviors in school-aged children: global trends in education, socioeconomic status, and adolescent health - Mastour Saeed Alshahrani; Vamsi Krishna Gannamaneni; Venkata Nagaraj Kakaraparthi; Khalid A. Alahmari; Batool Alkhamis; Ravi Shankar Reddy; Jaya Shanker Tedla; Snehil Dixit; Lalitha Kakaraparthi; Gopal Nambi (Frontiers in Public Health)
The study explores global trends in adolescent health using data from the health behavior in school-aged children (HBSC) study, focusing on the role of education, socioeconomic status, and school-based health programs. It examines cross-country comparisons to assess disparities in adolescent wellbeing and health behaviors. Findings highlight that nations with comprehensive public health policies report lower adolescent obesity rates and better mental wellbeing, whereas regions with limited resources, experience greater health inequalities. The key factors contributing to these disparities include economic conditions, access to healthcare, and variations in school health programs. The study underscores the need for evidence-based, culturally adaptable interventions to improve adolescent health outcomes. By analyzing current policies and identifying gaps, this review aims to guide future public health strategies toward reducing inequalities and strengthening school-based health initiatives worldwide.